2016
DOI: 10.1515/mammalia-2015-0042
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variation in the body size of adult female sperm whales (Physeter macrocephalus) – an example of McNab’s resource rule?

Abstract: Abstract:This study investigates possible regional variations in size composition of adult female sperm whales (Physeter macrocephalus) using data from 3302 pregnant individuals taken on Soviet whaling expeditions to the Southern Hemisphere 1961Hemisphere /62-1974. A general linear model (GLM) was used to take the covariates of expedition, latitude and ocean basin into account. The average body size decreased from south to north in each ocean basin, with the biggest decrease (about 200 cm) in the Indian Ocean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Lower latitudes have lower prey densities, favoring smaller body sizes ( McNab, 2010 ). Latitudinal gradients in marine mammal body size attributed to both Bergmann’s and McNab’s rules have been identified at broad taxonomic levels and between closely related species ( Galatius and Gol’din, 2011 ; Oosthuizen et al, 2016 ; Torres-Romero et al, 2016 ; Best et al, 2017 ; Ferguson et al, 2018 ; van Aswegen et al, 2019 ; Adamczak et al, 2020 ). For example, closely related pilot whale (Globicephala spp.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower latitudes have lower prey densities, favoring smaller body sizes ( McNab, 2010 ). Latitudinal gradients in marine mammal body size attributed to both Bergmann’s and McNab’s rules have been identified at broad taxonomic levels and between closely related species ( Galatius and Gol’din, 2011 ; Oosthuizen et al, 2016 ; Torres-Romero et al, 2016 ; Best et al, 2017 ; Ferguson et al, 2018 ; van Aswegen et al, 2019 ; Adamczak et al, 2020 ). For example, closely related pilot whale (Globicephala spp.)…”
Section: Methodsmentioning
confidence: 99%
“…In support of McNab’s rule, harbor porpoise populations along the California coast are larger than other populations, which may be driven by the nutrient-rich upwelling in this region ( Galatius and Gol’din, 2011 ). Additionally, latitudinal gradients in sperm whale body size have been linked to changes in prey size along this gradient ( Best et al, 2017 ). Similar trends are seen when comparing the recently diverged California sea lion and Galápagos sea lion ( Zalophus wollebaeki ).…”
Section: Methodsmentioning
confidence: 99%
“…Best et al [42] shown that there is a strong geographical variation in body size of adult sperm whales and, as a rule, individuals collected in tropical waters are significantly smaller than those in temperate regions. The factors that could produce such diversity in size include a different prey availability, which directly influences energy intakes and growth rates, or even that different populations have differing prey preferences that they occupy different geographical regions.…”
Section: Discussionmentioning
confidence: 99%